MODERN THERAPEUTIC APPROACHES IN CHRONIC INTERNAL DISEASES: STABILIZATION OF THE CONDITION AND ENSURING QUALITY OF LIFE - Vokhidjon Khatamov (Modern American Journals, 2025)
Chronic internal diseases — including arterial hypertension, diabetes mellitus, heart failure and chronic obstructive pulmonary disease — pose a major threat to public health worldwide. This article reviews modern therapeutic approaches aimed at effectively managing these diseases and improving the quality of life of patients. Advanced treatment strategies, including individualized therapy, optimized use of drugs, lifestyle changes, integrated methods of diet, rehabilitation and psychological support, are reviewed. The positive contribution of telemedicine and digital health technologies to therapeutic practice is also analyzed. The article is of practical and theoretical importance for therapists working with patients with chronic diseases, and includes recommendations for stabilizing the disease state and ensuring long-term control.
Keywords: Chronic internal diseases, therapeutic approach, individualized treatment, quality of life, diet, rehabilitation, telemedicine, health technologies.